Students Lived Experience in the Ethical Challenges of E-Learning: An Interpretive Phenomenological Study - Mirmoghtadaie Zohrehsadat; Soleiman Ahmady; Leili Borimnejad (International Journal of Qualitative Research, 2022)
Professional ethics is the most important issue nowadays and should be considered in e-learning more than in face-to-face education. This study was conducted by the hermeneutic phenomenology of the lived experience of e-learning graduate students who had registered virtually. Seven students were selected by Purposeful sampling. The selection of participants was done voluntarily. The interviews were conducted I September 2020 to July 2021. The data collection method was a virtual semi-structured interview and the interview analysis method was Diekelmann, Allen Tanner. Lincoln and Guba's criteria were used to ensure the Credibility, Transferability, and Dependability of the data. The main theme was “ethics of emphasis on words and neglected in action”, which was obtained from three sub-themes: “intentional and unintentional plagiarism”, “student exploitation” and “disregard for human dignity”. The present study showed that academic dishonesty had been experienced by students and this event affects the opinions about the quality of e-learning courses and even the reputation of the institutions offering these courses. It is suggested that more research be done in this field to identify the influential layers of faculties 'behavior on students' attitudes and performance.